Development Of An Internet Based Rating System For Ecotourism Sites - Shokouhi, Mohammad (2003)
In recent years, engineers, economists, and industry professional have placed an increasing emphasis on rating product, to know their quality. The Internet based rating system is an informative system, which is designed to inform visitors about the current state of rated object, which is related to a selected scenario for rating. To help users in making decision on the choice of objects that users are going to use, buy, visit etc, the Internet based rating system is designed to provide complete information on objects within its website. There are three types of entries allowed in the system such as site visitors, moderators and appointed auditors. As a testing system, the Malaysian ecotourism site has been selected for rating. The adapted rating system will be helpful for people and Malaysian government, especially ecotourism operator to know more about ecotourism site in Malaysia. Other countries can use the developed system as well.The system is flexible such that it can be used to rate a wide variety of objects on multiple levels.